2015
DOI: 10.1017/s1049023x15005038
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Tympanic Temperature Measurement in Firefighters Completing a Simulated Structural Firefighting Task

Abstract: Tympanic thermometers cause an unreliable measure of core body temperature for firefighters engaged in fire suppression activities. Accurate and practical measures of core body temperature are required urgently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Five studies analyzed the potential of in-ear T measurements for occupational medicine for prevention of heat illness (Nagano et al, 2010 ; Lee et al, 2011 ; Pryor et al, 2012 ; Keene et al, 2015 ; Nakada et al, 2017 ). The studies reported controversial results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies analyzed the potential of in-ear T measurements for occupational medicine for prevention of heat illness (Nagano et al, 2010 ; Lee et al, 2011 ; Pryor et al, 2012 ; Keene et al, 2015 ; Nakada et al, 2017 ). The studies reported controversial results.…”
Section: Resultsmentioning
confidence: 99%
“…Nagano et al showed that tympanic T, measured by a thermocouple probe with tight sealing in the ear canal, closely tracked both esophageal and rectal T with slight underestimation during simulated rest-work cycles at increasing environmental T (Nagano et al, 2010 ). IR tympanic probes underestimated core T obtained by gastrointestinal pills in firefighters performing work in heat chambers (bias ranging from 1.3 ± 0.5°C to 1.0 ± 0.8°C when entering the chamber and following exercise) (Keene et al, 2015 ) and during exercise with thermal protective clothing in a warm room (Pryor et al, 2012 ). By using a telemetry system consisting of an ear probe with IR sensor technology, a transmitter, and a wireless data receiver, Lee and co-workers showed an overall high level of agreement between tympanic and rectal T, both at rest and during exercise conditions, in healthy volunteers, although bias varied with clothing levels.…”
Section: Resultsmentioning
confidence: 99%
“…Inclusion in the present review was assessed against the following research criteria prior to data analysis; original research on human participants, body heat storage induced by physical activity, minimum pre-treatment T c of 38.2 °C reflecting the lowest anticipated T c during arduous emergency responses, minimum of five continuous minutes of immersion, provision of sufficient detail to reproduce methodology and valid T c measurement. Specifically, those studies reporting tympanic temperature data were excluded due to lack of validity [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…To be able to predict whether a firefighter is at risk of overheating is therefore of utmost importance. There are different ways to measure core temperature during physical activity ("A Pill that tracks your core body temperature using bluetooth technology and radio frequency," 2013), (Keene, Brearley, Bowen, & Walker, 2015),("The iDOT Body Temperature Alert Patch," 2011). One of the possibilities is a thermometer pill ("Thermometer Pill' Helps Athletes, Firefighters and Other Beat the Heart," 2006).…”
Section: Heat Stress Monitoringmentioning
confidence: 99%
“…Other possibilities to measure core temperature could be an ear thermometer (Keene et al, 2015) or a patch behind the neck ("The iDOT Body Temperature Alert Patch," 2011). We did not choose the ear thermometer because its core temperature measurements are not yet reliable enough because of environmental influences (Keene et al, 2015). The patch behind the neck is also not yet practical for firefighters because it requires very careful placement and isolation of the sensor.…”
Section: Heat Stress Monitoringmentioning
confidence: 99%